Ten years after the first oil crisis— OPEC's past and future - Klaus Matthies (Intereconomics, 1983)
In October 1973 OPEC sprang the first “oil shock” on the oil-importing countries. The member states took over the pricing of their petroleum and within three months prices had climbed to an unprecedented level. Only then did OPEC impress itself upon the public consciousness, although the organisation had been set up as long ago as 1960. Now, ten years later, the continuing oil glut has created the most difficult situation the organisation has faced since its inception. Is OPEC now slipping from the position it won in the seventies?
Keywords: 330